EVALUASI TERHADAP SEKOLAH KHUSUS OLAHRAGAWAN SMP/SMA RAGUNAN JAKARTA - Achmad Sofyan Hanif (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: An Evaluation of Special Schools for Athletes (SMP/SMA Ragunan Jakarta). This evaluation study aims to obtain information about the implementation of the training program by the special schools for athletes (SMP/SMA Ragu- nan), academic and sports achievements, recruitment, motivation, social system, communication, information, and services for the students. The sample consisted of 121 students, specially recruited by the Ministry of Youths and Sports, and 16 coaches/assistants randomly selected. The data were collected through questionnaires, interviews, and documents, and were analyzed using the descriptive technique. The results show that the school is still needed in accordance with the needs for the sports development in the country, it has not possessed a clear institutional management system, and it is necessary to make new agreements in the form of MOU to regulate the school management by involving relevant institutions. Keywords: evaluation, athletes, special school